DEVELOPMENT OF TECHNOLOGY FOR OBTAINING A DRY EXTRACT FROM THE SEDATIVE COLLECTION “LEFOSED” BASED ON LOCAL MEDICINAL PLANTS - Matazimov Muhammadjon Toxirjon o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2022)
The data from the «State Register of Medicines, Medical Devices, and Medical Equipment Approved for Use in Medical Practice of the Republic of Uzbekistan» for 2015-2020 were used to conduct this study. The study of the data showed that the share of medicines produced in the CIS countries accounts for 23 to 27 names, while the share of foreign medicines accounts for 19 to 26 names of medicines, the dynamics of which during 2015-2020 hasn't changed. In the same period, the share of domestic producers increased from 29 to 47 items.